Designing Nanoconfined LiBH4 for Solid-State Electrolytes - Suwarno, Suwarno; Nale, Angeloclaudio; Suwarta, Putu; Wijayanti, Ika Dewi; Ismail, Mohammad (Frontiers in Chemistry, 2022)
Solid-state electrolytes are necessary for high-density and safe lithium-ion batteries. Lithium borohydride (LiBH4) is one of the hydride compounds that shows promising candidates for solid-state electrolytes and enables all-solid-state batteries. LiBH4 has good wetting properties and preferable mechanical properties when used in the battery cells. The Li-ion conduction in LiBH4 can be modified with nanoconfinement as a result of distinct properties on the interfaces. The ion conductivities can be modified further by choosing properties support materials, i.e., composition, textural properties, and surface chemistry. The present work briefly reviews the Li-ion conduction in nanoconfined LiBH4. A future perspective on the development of LiBH4 as a solid-state electrolyte is further elaborated in the last section.